In Vitro Antidiabetic, Antioxidant, and Prebiotic Activities of the Chemical Compounds Isolated from Guizotia abyssinica - Ahmed Elbermawi; Mohamed Samir Darwish; Ahmed A. Zaki; Noha A. Abou-Zeid; Mohamed A. Taher; Ebtihal Khojah; Somaiah A. Bokhari; Amal F. Soliman (MDPI AG, 2022)
India and Ethiopia employ Guizotia abyssinica (niger plant) as a source of edible vegetable oil. Previous studies have documented the niger plant's antioxidant properties and dietary benefits. Here, G. abyssinica extract was obtained and ten known bioactive components (1-10) were isolated. The antioxidant, antidiabetic, and prebiotic properties of whole extract and isolated components of niger and the plant's ability to cooperate symbiotically with probiotic strains were examined. Compound 10, myricetin-3-O-L-rhamnoside, had the highest antioxidant capacity measured in the 2,2-diphenylpicrylhydrazyl (DPPH, 4629.76 ± 6.02 µmol Trolox equivalent/g compound) and ferric-reducing antioxidant power (FRAP, 2667.62 ± 7.5 mol Trolox equivalent/g compound) assays. The lowest α-amylase and glycogen phosphorylase activities and glucose diffusion were obtained with whole G. abyssinica extracts, whereas compounds 8-10 had moderate inhibitory effects. G. abyssinica extract also induced the highest glucose absorption by yeast cells in the presence of 5 mM of glucose. Moreover, Lactobacillus plantarum and L. rhamnosus incubated with β-sitosterol 3-O-D-glucoside (compound 7) showed the highest prebiotic activity score. The levels of L-(+)-lactic acid isomer in the probiotic strains were the highest in presence of the whole extract and decreased progressively in the presence of flavonoid glycosides (compounds 8-10) and β-sitosterol 3-O-D-glucoside. The enzymatic profile of the probiotic strains was unaffected by the niger extract and compounds 7-10. The findings revealed that the biological activities of G. abyssinica extract are mediated by the compounds 1-10, and it may be considered as a promising plant for the treatment of diabetes mellitus.